Building Environmental Awareness based on Science and Technology Society among MI Students - Sulthon Sulthon (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2020)
This research aimed to know the implementation of social studies learning at Madrasah Ibtidaiyah (MI, Islamic primary school) and to know how to build environmental awareness through social studies learning at MI. This was a library research involving a variety of sources particularly books and journal articles on social studies learning. The journal articles on social studies learning ranging from 2009 to 2018 and books on social studies learning from 2005 to 2009 were analyzed and synthesized. The results showed that social studies learning in MI have been carried out conventionally where teachers teach only by the lecturing method, less use of media oriented towards social problems in students’ daily lives. Meanwhile, environmental awareness character in community technology science-based social studies learning in MI was done by providing a social issue or problem, observing or researching social problems to be discussed as problem exploration, applying the concept by providing solutions to problems, conceptualization and assessment.